Balloon aortic valvuloplasty in the TAVR era: Not so new but definitely improved. Issue 2 (1st August 2017) - Feldman, Ted; Guerrero, Mayra
Key Points: BAV in the TAVR era is not well studied BAV resulted in improvements in aortic valve area and transvalvular pressure gradient, and in patients with impaired left ventricle function, ejection fraction improved. These improvements diminished over time, but at one year were still improved compared to baseline. BAV resulted in changes of planned therapy more than half of the patients treated as bridge for TAVR did not ultimately undergo TAVR twice as many planned as bridge for surgical valve replacement actually had surgical valve replacement. BAV techniques remain unstandardized and can be improved